The use of chitosan as alternative to bentonite for wine fining: Effects on heat-stability, proteins, organic acids, colour, and volatile compounds in an aromatic white wine. (30th October 2018) - Colangelo, Donato; Torchio, Fabrizio; De Faveri, Dante Marco; Lambri, Milena
Highlights: A dose of 1 g/L of fungoid chitosan was used for fining an aromatic white wine. Removal of chitinases and negligible depletion of thaumatins were observed. The heat stability of the fined chitosan wine samples was highly improved. Tartaric and malic acid, potassium and iron as well as free terpenols were reduced. The glycosylated terpenols and the fermentative aroma compounds were not affected. Abstract: This investigation focuses on the use of chitosan treatment simulating a bentonite fining in order to detect any modification of the wine haze potential by simultaneously evaluating the secondary effects on untargeted fixed and volatile compounds. A significant removal of chitinases was observed after fining an aromatic white wine with 1 g/L of a fungoid chitosan. Even if the more stable thaumatin like protein fractions were not significantly affected, the heat stability of the fined chitosan wine samples were highly improved in the 55–62 °C range. Among the secondary effects of a fining treatment, a reduction of tartaric acid, malic acid, potassium and iron was showed. All the free terpenols with the exception of α-terpineol were reduced in significant amounts, whilst the glycosylated forms and the fermentative aroma compounds were not affected by a 1 g/L chitosan addition.